Towards cost modelling for laser drilling process - Sarfraz, Shoaib; Shehab, Essam; Salonitis, Konstantinos; Suder, Wojciech; Sajid, Muhammad (IOP Publishing, 2018)
Laser drilling is a widely used non-traditional machining process, in power generation and high-value manufacturing industries, to produce components such as nozzle guide vanes, combustion chambers, fuel injection nozzles and turbine blades. The operating cost of the drilling process is one of the critical factors for companies to consider to survive in the competitive global market. This research is intended to develop the cost model for laser drilling process due to its extensive application in the aerospace sector. Cost estimation facilitates the aerospace sector economically through the identification of critical parameters which act as key cost drivers and their relationship with cost. The proposed model will benefit the designers and cost engineers to have a brief overlook of cost distribution before manufacturing the component.
Keywords: Laser drilling; process capability; cost modelling; cost driver